Relationship Between Arm Span Measurements and Body Height in Herceg Novi - Katarina Dragutunovic (Journal of Anthropology of Sport and Physical Education)
The aim of this study was to examine the height of the body in the Montenegrin adolescents from Hreceg Novi, as well as the relationship between the arm span and the body height, as a possible predictor of body height. The research was carried out on 58 Montenegrin adolescents from the southern region of Montenegro, of which 20 are men of average age 18.10 ± 0.55 years and 38 girls of the average age are 17.97 ± 0.37 years. Anthropometric measurements were carried out in accordance with the International Society for the Improvement of Kinanthropometry (ISAK) protocol. The correlation between body height and arm span was done by a correlation analysis with a confidence of 95%. Then, a linear regression analysis was performed to examine the degree to which the range of the arm can reliably predict growth. The results show that men adolescents are 183.97 ± 8.67 cm high and have arm span of 185.19 ± 9.58 cm, while girl adolescents are 168.75 ± 6.09 cm high and have arm span of 168.32 ± 7.20 cm. Compared to other studies, the results have shown that both sexes have made the people of Herceg Novi of the highest peoples than most of the nation across Europe. On the other hand, the range of arm span reliably predicts the height of the body in this part of Montenegro, in both sexes. This research was carried out due to the need to create a special height model for each region in Montenegro.